Membangun Desa Mallongi-Longi Melalui Program Prisma (Proyek Mini Infrastruktur Matematika) - Syafruddin Side; Irwan; Fitrah Mallolongeng; Nora Auliya Zahra; Syarif Hidayat (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
Mallong-Longi Village, Lanrisang District, Pinrang Regency, South Sulawesi Province is the location for the 2022 UNM KKNT team from the 2019 Mathematics study program. The people of Mallongi-Longi Village are mostly farmers/planters. The problem that is still faced by the village community is that the healthy environment in their homes and surroundings has not been maximized. The solution to this problem is to implement the Building Mallongi-longi village through the PRISMA Program to carry out cleaning and mutual cooperation activities for community service activities so that a Clean village environment is obtained. Furthermore, from the solution above, a work program was formed in the form of PRISMA Day, then the method of activity used by the work program was to carry out a Mathematical Infrastructure Mini Project. The results obtained during the implementation of the work program were Making a Vision-Mission Board for the Mallongi-Longi Village Office, Doing Community Service, Painting Village Boundaries, and Making Garbage Board Warnings.